2017
DOI: 10.1159/000460005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Loading Improves Tendon-Bone Healing in a Rabbit Anterior Cruciate Ligament Reconstruction Model by Promoting Proliferation and Matrix Formation of Mesenchymal Stem Cells and Tendon Cells

Abstract: Background/Aims: This study investigated the effect of mechanical stress on tendon-bone healing in a rabbit anterior cruciate ligament (ACL) reconstruction model as well as cell proliferation and matrix formation in co-culture of bone-marrow mesenchymal stem cells (BMSCs) and tendon cells (TCs). Methods: The effect of continuous passive motion (CPM) therapy on tendon-bone healing in a rabbit ACL reconstruction model was evaluated by histological analysis, biomechanical testing and gene expressions at the tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 56 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…Mechanical loading plays an important role in regulating skeletal tissue homeostasis; thus, a number of studies have been conducted to investigate the effects of mechanical stimulation on skeletal cells, including osteoblasts, chondrocytes, skeletal muscle cells, and endothelial cells. It has been shown previously that cell proliferation of human tendon cells [22], as well as venous smooth muscle cells [23], was improved by cyclic stretch. In this study, we treated cells with longitudinal stretch with 2.5% and 5% magnitude to mimic physiological loading and found that appropriate mechanical stimulation increased cell proliferation of BM-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical loading plays an important role in regulating skeletal tissue homeostasis; thus, a number of studies have been conducted to investigate the effects of mechanical stimulation on skeletal cells, including osteoblasts, chondrocytes, skeletal muscle cells, and endothelial cells. It has been shown previously that cell proliferation of human tendon cells [22], as well as venous smooth muscle cells [23], was improved by cyclic stretch. In this study, we treated cells with longitudinal stretch with 2.5% and 5% magnitude to mimic physiological loading and found that appropriate mechanical stimulation increased cell proliferation of BM-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical force may influence the healing potential as well. Song et al 22 demonstrated in a rabbit ACL reconstruction model that proliferation and differentiation of local precursor cells could be enhanced by mechanical stimulation. The relative low potential in the reattachment group assessed in this study may reflect the healing potential after mechanical stimulation of the attached cells.…”
Section: Discussionmentioning
confidence: 99%
“…This could be significant because this would alter the strain through the graft, and tendon-bone healing is influenced by changes in ACL graft force with joint motion. 40 , 41 The decision to evaluate suspensory fixation was made based on its popular usage in the UK, but the fact that suspensory fixation is popular does not necessarily mean it is the correct fixation to use. For instance, the use of interference screw fixation in both the femoral and tibial tunnel has been shown to have good results 15 years postoperatively with respect to objective and subjective outcomes, and to ligamentous stability.…”
Section: Discussionmentioning
confidence: 99%